ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA DENGAN PROFITABILTAS SEBAGAI VARIABEL MODERASI - Andhi Adhitya Nurcahyo; Rossje V Suryaputri (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2014)
The objective of the empirical study is to examine and to analyze the effect of Board of Directors, Leverage, Perccntage of Public Stock and Firm Size to Earning Management with Profitability as a moderated variable. The sample of this empirical study is the manufacturing company that listed in Indonesia Stock Exchange (IDX) in 2011-2014. Total sample of this research is 96 financial statement. This research uses multiple regression analysis as hypotesis testing. The result of this empirical study are board of directors, percentage of public stock and firm size has not significant influence to earnings management, leverage has significant influence to earnings management. Board of directors which moderated of profitability, leverage which moderated of profitability and firm size which moderaed of profitability has not significant influence to earnings management, percentage of public stock which moderated of profitability has significant influence to earnings management.